Effect of circuit weight training on aerobic fitness, body fat percentage, muscle mass percentage, and hand grip strength in the elderly - Intan Suraya Ellyas; Sunardi Sunardi; Muhammad Mariyanto; Sarjoko Lelono; Agus Margono; Agus Kristiyanto (Jurnal Keolahragaan, 2023)
The purpose of this study was to determine the effect of weight training using circuit methods on aerobic fitness, body fat percentage, muscle mass percentage, and hand grip strength. This study is a one-group pretest-posttest quasi-experimental study with a sample of the elderly gymnastics group Sehat Bugar Ceria in Karanganyar Regency, Indonesia. Twenty-seven study subjects aged 60–75 participated in the exercise for 12 meetings. All research subjects can take all pretests and posttests in the form of a six-minute walk test, a hand grip strength test using a handgrip dynamometer, and body composition testing using bioelectrical impedance analysis. Changes that occurred before and after exercise were analyzed using paired t-tests. This study showed that aerobic fitness increased significantly (p = 0.001), body fat percentage decreased significantly (p = 0.008), but there was no significant change in the percentage of muscle mass (p 0.05) or hand grip strength (p 0.05). The results of this study showed that weight training using circuit methods can improve aerobic fitness and reduce body fat percentage in the elderly group.